Instagram influencers and brand awareness: the impact on the youth followers in Singapore - Jiayan, Natalie Wong; Talib, Ameen (Ifma Publishing, 2022)
Due to the proliferation of social media, such as Instagram and its influencers, brands have begun to leverage on the latter’s large following to generate brand awareness for their products. The objective of this study was to conduct an exploratory research to examine if Instagram influencers have any impact on brand awareness. The study employed the use of focus groups and online questionnaires to gather primary data about the users’ motivations behind following such influencers. Multiple regression techniques were used to calculate the significance of the independent variables of the study. It was found that followers were more likely to have a negative opinion of influencers, as compared to a positive opinion. Despite this, it was also found that they continue to follow them on Instagram due to the three main themes that were identified: an attractive influencer, a high number of followers, and nicely taken pictures. In addition, it was observed that the brand awareness that followers receive through an Instagram influencer’s post, does not make any significant impact on the purchase intention of that product.